Phenolic compounds in enhancing physical barrier and suppressing growth of Ganoderma boninense PER71 - Ganapathy, Daarshini (2022)
Oil palm (OP) is one of the dominant plantation crops that bring so much abundance to many countries in terms of economic value, quality goods, and food products. However, the production of oil palm is hindered to a great extent, facing a devastating issue which started to decline in the cultivation of palm oil caused by basal stem rot (BSR) disease. Ganoderma boninense is the whiterot basidiomycetes, the primary causal pathogen of BSR. This pathogen invades via roots and degrades the lignin and cellulose components. Many approaches are available in controlling BSR, although, there is no effective method to suppress G. boninense completely. An alternative way to control the disease is to safeguard the physical barriersand inhibit the production of ligninolytic and hydrolytic enzymes by pathogen. Gallic acid (GA), thymol (THY), propolis (PRO), and carvacrol (CARV) were used to study the effects of phenolic compounds on the growth of G. boninense PER71, as well as to determine how well they may suppress the development of ligninolytic and hydrolytic enzymes. These four phenolic compounds with different concentrations were able to inhibit the growth of G. boninense PER 71 at different levels. Based on the study, mycelia grown on media containing the phenolic compounds showed greater inhibition at the highest concentration (GA 8 mg/ml, THY 0.25 mg/ml). Significant differences (p<0.05) were observed and 94% inhibition was exerted by GA. The mycelial morphology under scanningelectron microscopy (SEM) and high-resolution transmission electron microscopy (HR-TEM) revealed that phenolic compounds have a greater impact on mycelial structure, cell wall and cell membrane. The fungal membrane integrity and permeability tested with a flow cytometer exerted severe damage to the mycelium treated with GA and THY and reported the highest amount of sugar (monosaccharides-glucose) and electrolyte leakage. The ergosterol content present in the G. boninense PER71 was very much interrelated with the morphological disruptions. Furthermore, to justify the findings, suppression of hydrolytic and ligninolytic enzymes secreted by G. boninense PER71 with the application of phenolic compounds were determined. The phenolic compounds had shown inhibitory effects and a significant (p<0.05) decrease in the secretion of enzymes. Among the phenolic compounds tested, GA was the most effective compound in suppressing the hydrolytic and ligninolytic enzymes followed by THY. The PRO and CARV had some suppression on these enzymes but were not as effective as the other two. The antifungal efficacyof the phenolic compounds during the studies indicated the consistency in eliminating the G. boninense PER71. Moreover, the effectual mode of delivery of the phenolic compound (encapsulation of beads) and characterization were performedto validate the structure, quality and release of the phenolic compound via SEM and High Performance Liquid Chromatography (HPLC). The freshly encapsulated beads showed >90% of inhibitory effect on G. boninense PER71. This study proposed that GA and THY could be developed further as naturally occurring phenolic compounds and deliver new strategies to eradicate the G. boninense and finally could be used to control the BSR disease.